2019
DOI: 10.1016/j.jtcvs.2018.08.089
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stenosis of the neonate: A single-center experience

Abstract: Objectives: Because data for neonates are limited, optimal management of critical aortic stenosis remains controversial (balloon valvotomy [BV] or open valvoplasty [OV]). In a center with balanced experience in both methods, we hypothesized that OV can provide a better individualized approach than blunt BV and better serve long-term outcomes.Methods: A retrospective review of data and follow-up (survival, freedom from operation/replacement) of all neonates, suitable for biventricular repair, undergoing aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 26 publications
(48 reference statements)
4
47
1
Order By: Relevance
“…In the current literature, a longer freedom from reintervention is generally reported after surgical valvotomy than after balloon valvotomy, with freedom from reintervention at 10 years after surgical valvotomy of between 35 and 68%. 5,8,14,15,17 This was confirmed in a recent publication by Vergnat et al 18 In our study, statistical comparison between surgical and balloon valvotomy is not fruitful, as only six patients had a primary balloon valvotomy.…”
Section: Discussionsupporting
confidence: 76%
“…In the current literature, a longer freedom from reintervention is generally reported after surgical valvotomy than after balloon valvotomy, with freedom from reintervention at 10 years after surgical valvotomy of between 35 and 68%. 5,8,14,15,17 This was confirmed in a recent publication by Vergnat et al 18 In our study, statistical comparison between surgical and balloon valvotomy is not fruitful, as only six patients had a primary balloon valvotomy.…”
Section: Discussionsupporting
confidence: 76%
“…In young infants, Vergnat et al 4 reported SAVachieved better results, while ours, excluding neonates, was comparable. Small anulus and extremely fused valve made it hard to identify and repair the valve by surgery.…”
Section: Discussionsupporting
confidence: 46%
“…In the neonate with ductal-dependent systemic circulation, the key issue is to decide whether left-sided structures are adequate to sustain the systemic circulation, and if so, what kind of treatment is the most beneficial [15,16]. Various predictive formulas [17,18] have been proposed and are often calculated, but minor changes in measurements can result in opposite recommendations, the algorithms can conflict with each other, and there is no consensus on what is definitively required to establish a successful biventricular correction [16].…”
Section: Decision-making Critical Aortic Stenosismentioning
confidence: 99%
“…Neonatal Critical Aortic Stenosis Surgical Management: Open Valvotomy Open valvotomy has been advocated by several recent publications [15,[22][23][24][25][26] as it allows construction of a cusp anatomy that is as close as possible to the normal anatomy. Shaving of thickened cusps, excision of obstructive myxomatous nodularities, and mobilization of the cusps effectively increase the orifice area of the valve in any type of morphology, with a minimal risk of creating regurgitation (Fig.…”
Section: Surgical and Interventional Managementmentioning
confidence: 99%